Galectin-9 is required for endometrial regenerative cells to induce long-term cardiac allograft survival in mice - Yiming Zhao; Xiang Li; Dingding Yu; Yonghao Hu; Wang Jin; Yafei Qin; Dejun Kong; Hongda Wang; Guangming Li; Alessandro Alessandrini; Hao Wang (Stem Cell Research & Therapy, 2020)
Abstract Background Endometrial regenerative cells (ERCs), a novel type of mesenchymal-like stem cells, were identified as an attractive candidate for immunoregulation and induction of cardiac allograft tolerance. However, the underlying mechanisms of ERCs in immune regulation still remain largely unclear. The present study is designed to determine whether the expression of Galectin-9 (Gal-9), a soluble tandem-repeat member of the galectin family, is crucial for ERC-based immunomodulation. Methods In this study, we measured Gal-9 expression on ERCs and then co-cultured Gal-9-ERCs, ERCs, and ERCs+lactose (Gal-9 blocker) with activated C57BL/6-derived splenocytes. Furthermore, we performed mouse heart transplantation between BALB/c (H-2d) donor and C57BL/6 (H-2b) recipient. ERCs were administrated 24 h after the surgery, either alone or in combination with rapamycin. Results Our data demonstrate that ERCs express Gal-9, and this expression is increased by IFN-γ stimulation in a dose-dependent manner. Moreover, both in vitro and in vivo results show that Gal-9-ERC-mediated therapy significantly suppressed Th1 and Th17 cell response, inhibited CD8+ T cell proliferation, abrogated B cell activation, decreased donor-specific antibody production, and enhanced the Treg population. The therapeutic effect of ERCs was further verified by their roles in prolonging cardiac allograft survival and alleviating graft pathological changes. Conclusions Taken together, these data indicate that Gal-9 is required for ERC-mediated immunomodulation and prevention of allograft rejection.